Sexual orientation biases attentional control: a possible gaydar mechanism - Colzato, Lorenza S.; Van Hooidonk, Linda; Van Den Wildenberg, Wery; Harinck, Fieke; Hommel, Bernhard (Frontiers in Psychology, 2010)
Homosexuals are believed to have a “sixth sense” for recognizing each other, an ability referred to as gaydar. We considered that being a homosexual might rely on systematic practice of processing relatively specific, local perceptual features, which might lead to a corresponding chronic bias of attentional control. This was tested by comparing male and female homosexuals and heterosexuals--brought up in the same country and culture and matched in terms of race, intelligence, sex, mood, age, personality, religious background, educational style, and socio-economic situation--in their efficiency to process global and local features of hierarchically-constructed visual stimuli. Both homosexuals and heterosexuals showed better performance on global features—the standard global precedence effect. However, this effect was significantly reduced in homosexuals, suggesting a relative preference for detail. Findings are taken to demonstrate chronic, generalized biases in attentional control parameters that reflect the selective reward provided by the respective sexual orientation.